PENINGKATAN KEMAMPUAN MEMBACA INTENSIF MELALUI PENDEKATAN KONTEKSTUAL BERBASIS MASALAH PADA SISWA MTs NEGERI 1 BOJONEGORO - Nur Halimah (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2014)
This study was conducted in order to determine the ability of students to read intensively through contextual approach. to determine the extent to which students' reading abilities. meode used is the qualitative and quantitative methods for the study was conducted through the test process by looking at student work. This study uses classroom action research or PTK. This study was conducted at MTs Negeri 1 Bojonegoro class VIII A are 32 students sampled transform and research. Of the 32 children were divided into 8 groups with the number 1 group of 4 children. This studywas conducted on September 17, 2012 to October 30, 2012. In the pre-cycle in the form of discourse about teachers giving, students answer questions based on the discoursewas continued discussion in the form of class discussions, and intensive reading research results obtained by the average number of 66.37 or 66%. In the first cycle teachers began to apply a contextual approach to learning then students are given intensive reading about the discourse and to determine the increase after application of a contextual approach and the obtained results with the average amount of 80.46 or 80 average number of 88.12 or 88%. Learning outcomes intensive reading contextual approach suggests that the ability of students to understand the reading proved to increase, the increase is seen and the test results achieved by students at the pre-cycle with an average of 66.37 or 80.46 or 66% to 80% in Cycle I. While on cycle I previously with average 80.46 or 80% up to 88.12 or by 88%. In the second cycle based on the results achieved by students to increase reading skills to understand the content.